If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = (x) 0 = x Solving 0 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 0 + -1x = x + -1x Remove the zero: -1x = x + -1x Combine like terms: x + -1x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| X^2=188 | | =z+.9 | | cos((pi*x)/4) | | 5+7x=-25 | | -7x+2y=16 | | 1.2=120+0.01+t | | cos((pi*x))/4 | | 27=r/-4 | | 9+6x=-25 | | 2*d-2=20 | | 8x+6=-25 | | 1/3(d-8)-7/2(5d-3)=7/12 | | 7(1x-1)=-2(-4x+3) | | 3x+2(x-20)=510 | | .07t+.3(t+5)=3.35 | | a+3-2a=-1+3a+4 | | 3x+17.5+3.5x=24 | | 27x^2+18x=360x+72 | | G(x)=8tan(4x) | | -3(x+1)=39 | | f(x)=x^2+x-42 | | 3+5lnx=23 | | f(x)=-7x^2-14x-1 | | .8z=48 | | 15*(2*x)=45 | | 1.24y=-1.44 | | 4=x-y | | (2x-6)/7 | | 1.24y=1.44 | | 5d+2=4 | | 15*2x=45 | | 2t(1/2+5)=39 |